2017
DOI: 10.1002/smll.201603821
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conducting Spaced TiO2 Nanotubes Enable Defined Conformal Coating with Nanocrystalline Nb2O5 and High Performance Supercapacitor Applications

Abstract: Establishing self-organized spacing between TiO nanotubes allows for highly conformal Nb O deposition that can be adjusted to optimized supercapacitive behavior.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Differently, spaced (SP) TiO 2 nanotubular arrays that can be grown under specific anodization conditions offer a defined intertube spacing. Recently, it has been shown that spacing between NTs improves the accessibility of outer‐tube walls, and this results in better inter‐diffusion and the formation of interdigitated structures that often outperform CP tubes, even though as‐formed SP NTs have a less active surface area than conventional CP NTs …”
Section: Introductionmentioning
confidence: 99%
“…Differently, spaced (SP) TiO 2 nanotubular arrays that can be grown under specific anodization conditions offer a defined intertube spacing. Recently, it has been shown that spacing between NTs improves the accessibility of outer‐tube walls, and this results in better inter‐diffusion and the formation of interdigitated structures that often outperform CP tubes, even though as‐formed SP NTs have a less active surface area than conventional CP NTs …”
Section: Introductionmentioning
confidence: 99%
“…The α‐MnO 2 /N‐TiO 2 /SCFP electrode delivers a high areal capacitance of 400.3 mF cm −2 at a discharged current density of 1.3 mA cm −2 , which is significantly larger than that of the α‐MnO 2 /N‐TiO 2 /CFP electrode (277.2 mF cm −2 at 1.3 mA cm −2 ). Moreover, this value is also larger than the reported N‐TiO 2 composites, such as MnO x /N‐TiO 2 /CFP (327 mF cm −2 at 0.25 mA cm −2 ), TiN@MnO 2 coaxial arrays (41 mF cm −2 at 0.12 mA cm −2 ), 1 h‐TiN x O y /MnO 2 nanoarrays (160 mF cm −2 at 0.5 mA cm −2 ), and TiO 2 /Nb 2 O 5 /NH 3 (37 mF cm −2 at 0.25 mA cm −2 ) . Meanwhile, the MnO 2 /N‐TiO 2 /SCFP electrode also demonstrates a good rate capability.…”
Section: Resultsmentioning
confidence: 71%
“…Their unique properties, including high power density, fast charge/discharge rate, long cycle life and environmental friendliness, make supercapacitors attractive devices for a variety of applications in energy storage such as electronic communications, the emergent electric transportation industry and aerospace [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The energy storage mechanism of supercapacitors can be generally classified into two categories: electric doublelayer capacitance (EDLC) and pseudocapacitance [1,[11][12][13][14]. EDLC is based on the physical adsorption and desorption of ions at the interface between an electrolyte and electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation